A TRACER BUDGET QUANTIFYING SOIL REDISTRIBUTION ON HILLSLOPES AFTER FOREST HARVESTING - Wallbrink P.J.; Roddy B.P.; Olley J.M. (My University, 2002)
Managing the impacts of erosion after forest harvesting requires knowledge of erosion sources; rates of sediment transport and storage; as well as losses from the system. We construct a tracer-based (137Cs) sediment budget to quantify these parameters. The budget shows significant redistribution, storage and transport of sediment between landscape elements and identifies the snig tracks and log landings as the major impact sites in the catchment. Annual sediment losses from them were estimated to be 25+/-11 and 101+/-15 t ha-1 year-1, respectively, however, it is probable that most of this is due to mechanical displacement of soil at the time of harvesting. The budget showed greatest net transport of material occurring from snig tracks; representing some 11+/-4% of the 137Cs budget. Of the latter amount, 18%, 28% and 43% was accounted for within the cross banks, filter strip and General Harvest Area (GHA), respectively. The 137Cs budget also showed the GHA to be a significant sediment trap. The filter strip played a fundamental role in the trapping of material generated from the snig tracks, the mass delivery to them from this source was calculated to be 1.7+/-0.6 kg m2 year-1. Careful management of these remains critical. Overall we could account for 97+/-10% of 137Cs. This retention suggests that (within errors) the overall runoff management system of dispersing flow (and sediment) from the highly compacted snig tracks, by cross banks, into the less compacted (and larger area) GHA and filter strips has effectively retained surface soil and sediment mobilised as a result of harvesting at this site.
Keywords: SEDIMENT BUDGET; 137CS; TRACERS; SOIL REDISTRIBUTION; FOREST HARVESTING; SNIG TRACK EROSION; FILTER STRIPS